Advanced thermodynamics engineering / Kalyan Annamalai and Ishwar K. Puri. - Annamalai, Kalyan (CRC, 2001)
This volume seeks to lay a strong conceptual foundation and provide simple, physical explanations for thermodynamic processes and the practical evaluation of thermodynamic systems.